2012
DOI: 10.1038/ijir.2012.1
|View full text |Cite
|
Sign up to set email alerts
|

Impact of erectile function and age in men with lower urinary tract symptoms on ejaculatory dysfunction and premature ejaculation

Abstract: Lower urinary tract symptoms (LUTSs) and ED are clearly correlated, but to date no correlation with ejaculatory dysfunction (EjD) has been identified. Therefore, this study evaluated the impact of erectile function in men with LUTS on EjD and premature ejaculation (PE). Erectile function, PE and EjD of 239 men (mean age, 53.0±10.65 years), International Prostate Symptom Score (IPSS), International Index of Erection Function (IIEF), intravaginal ejaculatory latency time (IELT) and the seven-item Male Sexual Hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 27 publications
0
8
0
1
Order By: Relevance
“…Additionally, a significant increase in the PE ratio was observed as the severity of ED increased. However, in a Korean study of 250 men who visited a urology clinic with LUTS, no differences were detected in intravaginal ejaculatory latency time in men with varying ED severity [23]. This study had a relatively small sample size.…”
Section: Discussionmentioning
confidence: 98%
“…Additionally, a significant increase in the PE ratio was observed as the severity of ED increased. However, in a Korean study of 250 men who visited a urology clinic with LUTS, no differences were detected in intravaginal ejaculatory latency time in men with varying ED severity [23]. This study had a relatively small sample size.…”
Section: Discussionmentioning
confidence: 98%
“…Those aged ≥ 65 years and 46-64 were 3 times each more likely to have erectile dysfunction than those 45 years and below. Several studies have reported strong association between age and ED ( Johannes et al, 2000 ; Wagle et al, 2012 ; Hwa et al, 2012) . This could be as a result of the association between aging and many chronic disorders which are organic causes of ED such as hypertension, diabetes and dyslipidemia.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism by which tadalafil and other PDE5 inhibitors may improve ejaculation remains unclear but is likely multifactorial. Although erection is not a prerequisite for ejaculation to occur from a physiological perspective , EjD has been closely associated with ED . Restoration of erectile function has been correlated with increased overall sexual satisfaction and intercourse satisfaction, thus the improvements in the IIEF‐OS and IIEF‐IS domains with tadalafil treatment in men with ED and LUTS/BPH were likely associated at least in part with improvements in erectile function.…”
Section: Discussionmentioning
confidence: 99%